Genetic considerations for mollusk production in aquaculture: current state of knowledge - Astorga, Marcela P. (Frontiers in Genetics, 2014)
IIn 2012, world mollusk production in aquaculture reached a volume of 15,171,000 tons, representing 23% of total aquaculture production and positioning mollusks as the second most important category of aquaculture products (fishes are the first). Clams and oysters are the mollusk species with the highest production levels, followed in descending order by mussels, scallops and abalones. In view of the increasing importance attached to genetic information on aquaculture, which can help with good maintenance and thus the sustainability of production, the present work offers a review of the state of knowledge on genetic and genomic information about mollusks produced in aquaculture. The analysis was applied to mollusks which are of importance for aquaculture, with emphasis on the 5 species with the highest production levels. According to FAO, these are: Japanese clam Ruditapes philippinarum; Pacific oyster Crassostrea gigas; Chilean mussel Mytilus chilensis; Blood clam Anadara granosa and Chinese clam Sinonovacula constricta. To date, the genomes of 5 species of mollusks have been sequenced, only one of which, Crassostrea gigas, coincides with the species with the greatest production in aquaculture. Another important species whose genome has been sequenced is Mytilus galloprovincialis, which is the second most important mussel in aquaculture production, after M. chilensis. Few genetic improvement programs have been reported in comparison with the number reported in fish species. The most commonly investigated species are oysters, with at least 5 genetic improvement programs reported, followed by abalones with 2 programs and mussels with one. The results of this work will establish the current situation with respect to the genetics of mollusks which are of importance for aquaculture production, in order to assist future decisions to ensure the sustainability of these resources.